Use of silicone finger prostheses in amputee patients: An integrative review - François Isnaldo Dias Caldeira; Victor Alves Nascimento; Kellen Cristina da Silva Gasque; Marcela Filié Haddad (Wolters Kluwer Medknow Publications, 2021)
This study aimed to perform an integrative review of the literature on the use of silicone finger prostheses in amputee patients. Searches were performed in the PubMed, EMBASE, Web of Science, Scielo, and Cochrane Library databases until July 2021. Descriptors used in this article were: Silicone, finger, rehabilitation, and prosthesis. Clinical research and clinical reports on silicone finger prostheses, available in full and in English were included. Initially, 152 articles were identified. After establishing the inclusion/exclusion criteria, 23 studies were identified and constituted the final sample. Regarding the publication date of the included studies, 17.2% of them were published between 2012 and 2016. Most of the rehabilitations occurred in India (69.9%; n = 16), and the mean age of patients who used prostheses was 38.1 years. The level of scientific evidence of the included studies was IV and VI. Therefore, patients rehabilitated with silicone finger prostheses highlighted significant improvements in functional range of motion, restoration of self-esteem, advantages in psychological therapy, more pleasant social interaction, and changes in their quality of life.